Eksplorasi Berbagai Fungsi Mitokondria Melalui Pendekatan Meta-Analisis dalam Biologi Seluler - Muhammad Isrul; Adnan Adnan; Mutmainnah Nur Islamia (Spizaetus: Jurnal Biologi dan Pendidikan Biologi, 2025)
Mitochondria have long been known as the main energy producers in eukaryotic cells through oxidative phosphorylation. However, the development of molecular biology has revealed its multifaceted role in the regulation of apoptosis, cellular metabolism, calcium homeostasis, and immune responses. This study uses a meta-analysis approach to explore the various functions of mitochondria by integrating data from various scientific studies. Literature searches were conducted through scientific databases, namely publish or perish. Data obtained 300 with relevant studies consisting of 24 articles, and 1 book according to the inclusion criteria. The results of the analysis show that the complexity and contextual nature of mitochondrial function, which depends on cell type and physiological conditions, indicate its adaptability in maintaining cell survival. Mitochondria are multifunctional organelles that not only play a role as a center for energy production through oxidative phosphorylation, but are also involved in various important cellular processes, namely as a central regulator of cell vitality, controlling processes ranging from survival to programmed cell death. In addition, mitochondrial dysfunction is associated with various pathological conditions, including neurodegenerative diseases, metabolic disorders, and cancer. This comprehensive review provides new insights into the importance of mitochondria in both normal and pathological states and emphasizes the importance of a deeper understanding of mitochondrial mechanisms for the development of targeted therapies.